A damage evolution characterization method for coupled failure behavior of heterogeneous adhesive joints

Through the expansion of power-exponential fracture model and a specially made sample preparation device, the problem of inability to efficiently characterize the coupling failure behavior of heteroglobin joints in the prior art is solved, and the precise characterization of the impact-resistant energy absorption capacity of multi-material hybrid structures is achieved and promote.

CN116935997BActive Publication Date: 2025-02-14JIANGSU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310767086.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2025-02-14
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

The existing numerical characterization methods of heterogeneous glue joints cannot efficiently characterize their coupling failure behavior, resulting in a lack of relevant research on the impact energy absorption ability and damage evolution of multi-material mixed structure glue joints.

Method used

The coupling failure behavior of heterogeneous glue joints is accurately characterized by using extended power-exponent fracture model and a specially made DCB and ENF sample preparation device through a variety of experimental and simulations.

Benefits of technology

The efficient characterization of the coupling failure behavior of heteroglobin joints is achieved, and the understanding of the impact energy absorption ability of multi-material mixed structures is improved, and the method is efficient and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116935997B_ABST
    Figure CN116935997B_ABST
Patent Text Reader

Abstract

The present invention discloses a damage evolution characterization method for coupled failure behavior of heterogeneous adhesive joints, and constructs an extended power exponential fracture model for coupled failure of adhesive joints; a sample preparation device is used to prepare adhesive specimens with a cracked type I fracture mode and conduct a DCB experiment, and adhesive specimens with cracked type II and type III fracture modes are prepared and conduct an ENF experiment to obtain fracture toughness parameters; a sample preparation device is used to prepare adhesive specimens with type I and type II fracture modes of three different slopes of a base material A and a base material B of equal thickness, and DCB and ENF experiments are conducted respectively to obtain power exponent parameters; the extended power exponential fracture model into which the fracture toughness parameters and the power exponent parameters are substituted is used as a fracture model in a constitutive model of glue in a simulation of heterogeneous adhesive joints, and a simulation of coupled failure behavior of heterogeneous adhesive joints is realized. The present invention can efficiently characterize the coupled failure behavior of adhesive joints of multi-material hybrid structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to fracture failure analysis of adhesive joints, and in particular to a damage evolution characterization method for coupled failure behavior of heterogeneous adhesive joints. Background Art

[0002] The Energy-saving and New Energy Vehicle Technology Roadmap 2.0 states that "the carbon emissions of the automobile industry will peak in 2028 ahead of the national carbon reduction commitment, and the total carbon emissions will drop by more than 20% from the peak in 2035". Lightweighting of automobiles is of great significance to achieving the "dual carbon" goals. Common lightweighting methods include structural optimization, the use of advanced manufacturing processes, and the use of lightweight materials. Among them, the use of new lightweight materials such as composite materials and variable thickness plates can reduce the weight most directly and effectively. However, due to its own limitations, a single material cannot usually be fully applied to the entire body. In order to achieve an effective balance between part performance, lightweight and manufacturing costs, considering multi-material hybrid design and manufacturing is an important way to achieve lightweighting of automobiles. However, the connection process of multi-material hybrid structures is the main factor that determines their stiffness, strength, fatigue durability and safety. The bonding process can achieve high-strength connection of the same or different materials, and has the advantages of uniform stress distribution, light weight, and no damage to the bonded objects. It is an important development direction of future automotive multi-material hybrid structure connection technology.

[0003] The connection strength of adhesive joints in multi-material hybrid structures depends on the failure mode of the adhesive interface and the quality of the adhesive. The failure modes of heterogeneous adhesive interfaces are complex and diverse, mainly including cohesive failure of the adhesive layer, interface failure of the parent material side and mixed failure modes, which are related to factors such as loading conditions, adhesive type, parent material type and stiffness, and adhesive layer thickness. During the service of a car, traffic accidents and impacts from external objects may threaten the safety of the occupants. For a multi-material hybrid structure of a car, simply improving the strength of the adhesive joint cannot further improve the impact energy absorption requirements of the hybrid structure. It is necessary to ensure that the adhesive joint has sufficient fracture toughness to ensure that the car has sufficient impact energy absorption capacity in the event of a collision.

[0004] The adhesive specimens tested for fracture toughness usually present more than one failure mode, but a coupling of multiple failure modes. This makes the numerical characterization of the adhesive interface more complicated. The existing numerical characterization methods for the failure behavior of heterogeneous interfaces in adhesive joints have the following problems: ① Since the fracture toughness of the single-layer cohesive model is taken from the standard DCB (Double Cantilever Beam) or ENF (End Notched Flexure) test, it can usually only characterize the failure mode of cohesive failure of the adhesive layer; ② The method of modeling the interval between multi-layer cohesive units and adhesive shell units can simulate all possible failure modes separately, but cannot simulate the coupling behavior between different failure modes at the same time; ③ The ACDM-based adhesive layer refinement modeling method can simulate the coupling between heterogeneous interface failure modes, but this method is complex to model and has high computational cost.

[0005] In summary, the existing numerical characterization methods of heterogeneous adhesive joints cannot efficiently characterize their coupled failure behavior, and there is a lack of relevant research on the impact energy absorption capacity and damage evolution of the coupled failure behavior of hybrid structural adhesive joints. Summary of the invention

[0006] In view of the shortcomings in the prior art, the present invention provides a damage evolution characterization method for the coupled failure behavior of heterogeneous adhesive joints, which considers the influence of different thicknesses, parent material combinations and multiple failure modes coupled failure on the fracture energy absorption of adhesive joints, and efficiently characterizes the coupled failure behavior of adhesive joints of multi-material hybrid structures.

[0007] The present invention achieves the above technical objectives through the following technical means.

[0008] A damage evolution characterization method for coupled failure behavior of heterogeneous adhesive joints:

[0009] (1) Construct an extended power exponential fracture model for coupled failure of adhesive joints:

[0010]

[0011] Where: G interAIC , G interAIIC , G interAIIIC are the energy absorption values ​​of type I, type II and type III fracture modes of interface failure between adhesive and base material A under stress coupling state at the moment of fracture, G interBIC , G interBIIC , G interBIIIC are the energy absorption values ​​of type I, type II and type III fracture modes of interface failure between adhesive and base material B under stress coupling state at the moment of fracture, G GlueIC , G GlueIIC , G GlueIIICare the energy absorption values ​​of type I, type II and type III fracture modes of the adhesive failure under stress coupling state at the moment of fracture, G interAI , G interAII , G interAIII are the energy absorption values ​​of type I, type II and type III fracture modes of the interface failure between the adhesive and the base material A when they exist separately, G interBI , G interBII , G interBIII are the energy absorption values ​​of type I, type II and type III fracture modes of the interface failure between adhesive and base material B when they exist separately, G GlueI , G GlueII , G GlueIII are the energy absorption values ​​of the rubber when the type I, type II and type III fracture modes exist alone, and the power exponent α 1 and β 1 It represents the coupling effect of three different fracture modes on the fracture behavior of the adhesive and base material A under the failure condition. The power exponent α 2 and β 2 Indicates the coupling effect of three different fracture modes on the fracture behavior of the adhesive and base material B under the failure condition. The power exponent α 3 and β 3 It represents the coupling effect of three different fracture modes on its fracture behavior when the adhesive itself fails;

[0012] (2) Three groups of homogeneous bonding specimens with three fracture modes of interface failure between base material A and adhesive layer, three groups of homogeneous bonding specimens with three fracture modes of interface failure between base material B and adhesive layer, and three groups of heterogeneous bonding specimens with three fracture modes of self-cohesive failure of adhesive layer were prepared by DCB specimen preparation device and ENF specimen preparation device respectively. When preparing specimens with interface failure between base material and adhesive layer, a pre-crack of polytetrafluoroethylene film was placed between base material and adhesive layer to guide crack propagation and thus induce interface failure between base material and adhesive layer. When preparing specimens with self-cohesive failure of adhesive layer, a pre-crack of polytetrafluoroethylene film was placed in the middle of adhesive layer to guide crack propagation and thus induce cohesive failure of adhesive layer. DCB experiments were carried out on the three types of bonding specimens with type I fracture mode, and the experimental data were processed to obtain G interAI , G interBI , G GlueI ; ENF experiments were performed on three types of adhesive bonding tests with type II fracture mode, and the experimental data were processed to obtain G interAII , G interAIII , G interBII , G interBIII , G GlueII , G GlueIII ;

[0013] (3) The DCB specimen preparation device and the ENF specimen preparation device are used to prepare the bonding specimens of type I and type II fracture modes of the three types of base materials A with different slopes and base materials B with equal thickness respectively; the DCB test is carried out on the bonding specimens of type I fracture mode of the three types of base materials A with different slopes and base materials B with equal thickness respectively, and the ENF test is carried out on the bonding specimens of type II fracture mode of the three types of base materials A with different slopes and base materials B with equal thickness respectively; the force-displacement curve of each group of experiments is obtained from the experimental data and the corresponding fracture toughness value is calculated, each group of experimental working conditions is simulated, and the error analysis is carried out between the fracture toughness value obtained by the simulation result curve and the fracture toughness value obtained by the experiment through the updating and iteration of the power exponent. When RSME is less than 0.05, the accuracy requirement is met, and the power exponent of the simulation is the power exponent parameter required;

[0014] (4) Determine G interAI , G interBI , G GlueI , G interAII , G interAIII , G interBII , G interBIII , G GlueII , G GlueIII The sum power exponent is substituted into formula (1) and used as the fracture model in the constitutive model of the adhesive in the simulation of heterogeneous adhesive joints to realize the simulation of the coupled failure behavior of heterogeneous adhesive joints.

[0015] Furthermore, the sample preparation device includes a front plate, a rear plate, a bottom plate, a pressure plate, a sample, a gasket and a feed screw, wherein the bottom plate is stepped; the bottom of the front plate is mounted on a higher level of the bottom plate step, and the feed screw is mounted on the front plate; the bottom of the rear plate is mounted on a lower level of the bottom plate step, and the pressure plate is placed between the front plate and the rear plate, and is located on the lower level of the bottom plate step; grooves consistent with the size of the sample are respectively provided on the opposing surfaces of the pressure plate and the rear plate, and the depth of the grooves is lower than the thickness of the sample; when the device is in use, the gaskets are arranged at the upper and lower ends of the opposing surfaces of the rear plate and the pressure plate in the vertical direction.

[0016] Furthermore, the dimensions of the front plate and the rear plate on the horizontal plane perpendicular to the direction of the feed screw are consistent with those of the bottom plate, and the dimension of the pressure plate on the horizontal plane perpendicular to the direction of the feed screw is smaller than that of the bottom plate.

[0017] Furthermore, bosses are provided at both ends of the bottom plate on the moving path of the pressing plate toward the rear plate.

[0018] Furthermore, a sampling groove for convenient sampling is reserved at the upper end of the groove, and a channel for convenient processing is reserved at the lower end.

[0019] Furthermore, when preparing specimens with failure at the interface between the base material and the adhesive layer, a polytetrafluoroethylene film is first placed in the pre-crack area on the base material side and fixed on a pressing plate, and then glue is evenly applied to the adhesive areas of the specimens on both sides; when preparing specimens with cohesive failure of the adhesive layer itself, glue is first evenly applied to the adhesive areas of the specimens on both sides, and then a polytetrafluoroethylene film is placed in the pre-crack area in the middle of the adhesive layer and fixed on a pressing plate.

[0020] Furthermore, the thickness of the gasket is selected according to the thickness of the sample, and the thickness of the gasket is the sum of the thickness of the sample and the thickness of the adhesive layer minus twice the depth of the groove.

[0021] Furthermore, when conducting a DCB experiment, a connector and a tensile fixture are required. The upper end of the tensile fixture is the clamping end, and the lower end of the fixture is the sample connection end. Before the experiment, the connector and the sample are glued and cured together at a constant temperature. The pin at the lower end of the tensile fixture passes through the through hole in the middle of the connector to achieve the coordination between the connector and the tensile fixture.

[0022] Furthermore, when the DCB test was conducted on the bonded specimens of type I fracture mode of the three different slopes of the base material A and the base material B of equal thickness, the thickness of the adhesive layer of the bonded specimens was the same and did not change due to the change of the base material thickness; when the specimens broke under the experimental loading, multiple failure mode coupling failure occurred.

[0023] Furthermore, when the ENF test was conducted on the type II fracture mode bonded specimens of three different slopes of base material A and the same thickness base material B, the thickness of the adhesive layer of the bonded specimens was the same and did not change due to the change in the thickness of the base material; when the specimens were loaded in the experiment, the lower support roller on one side was higher than the lower support roller on the other side, so that the variable thickness specimen was supported by the lower support roller, and the upper surface of the specimen was squeezed by the upper support roller in a horizontal state.

[0024] The beneficial effects of the present invention are:

[0025] (1) The present invention includes two kinds of sample preparation devices, and DCB samples and ENF samples can be prepared by the two preparation devices; grooves consistent with the sample size are opened on the opposite surfaces of the pressure plate and the back plate, and when preparing the sample, the sample is placed in the groove to prevent the sample from moving; and when preparing the sample with interface failure between the base material and the adhesive layer, a polytetrafluoroethylene film is placed between the base material and the adhesive layer to pre-form cracks, guide the crack propagation, and thus induce interface failure between the base material and the adhesive layer; when preparing the self-cohesive failure of the adhesive layer, a polytetrafluoroethylene film is placed in the middle of the adhesive layer to pre-form cracks, guide the crack propagation, and thus induce cohesive failure of the adhesive layer, thereby realizing different failure modes; in addition, the thickness of the adhesive layer of the sample is controlled by a gasket, and when the base material thickness is different, the gasket of appropriate thickness can be selected according to the requirement of the adhesive layer thickness to accurately control the adhesive layer thickness of the bonded sample.

[0026] (2) The extended power exponential fracture model of the present invention can accurately characterize the coupled failure behavior of heterogeneous adhesive joints in the simulation of heterogeneous adhesive joints, which is of vital importance to the performance of the joints of heterogeneous adhesive hybrid structures under impact loads. The extended power exponential fracture model is efficient and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] FIG1( a ) is a schematic diagram of a type I fracture mode of an adhesive joint according to the present invention;

[0028] FIG1( b ) is a schematic diagram of a type II fracture mode of an adhesive joint according to the present invention;

[0029] FIG1( c ) is a schematic diagram of a Type III fracture mode of an adhesive joint according to the present invention;

[0030] FIG2( a ) is a schematic diagram of a DCB experiment according to the present invention;

[0031] FIG2( b ) is a schematic diagram of the ENF experiment of the present invention;

[0032] Figure 3 It is a schematic diagram of the positional relationship between the crack and the sample according to the present invention;

[0033] Figure 4 Schematic diagram of the parent materials with three slopes according to the present invention;

[0034] Figure 5 This is a schematic diagram of a bonding specimen with a slope of 3 according to the present invention;

[0035] Figure 6 This is a structural diagram of the DCB sample preparation device of the present invention;

[0036] Figure 7 This is a schematic diagram of the interior of the DCB sample preparation device of the present invention;

[0037] Figure 8 The second schematic diagram of the interior of the DCB sample preparation device of the present invention;

[0038] Fig. 9 This is a structural diagram of the ENF sample preparation device of the present invention;

[0039] FIG10( a ) is a structural diagram of a sample connector according to the present invention;

[0040] FIG10( b ) is a structural diagram of the stretching fixture of the present invention;

[0041] Fig.11 It is a flow chart of the damage evolution characterization method of the coupled failure behavior of heterogeneous adhesive joints according to the present invention;

[0042] Among them, 1-DCB sample preparation device, 101-tool 1 front plate, 102-tool 1 rear plate, 103-tool 1 bottom plate, 104-tool 1 pressure plate, 105-DCB sample, 106-tool 1 gasket, 107-tool 1 feed screw, 2-ENF sample preparation device, 201-tool 2 front plate, 202-tool 2 rear plate, 203-tool 2 bottom plate, 204-tool 2 pressure plate, 205-ENF sample, 206-tool 2 gasket, 207-tool 2 feed screw. DETAILED DESCRIPTION

[0043] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.

[0044] The present invention provides a damage evolution characterization method for coupling failure behavior of heterogeneous adhesive joints, see Fig.11 , the specific process is as follows:

[0045] 1. Extended power exponential fracture model for coupled failure of adhesive joints

[0046] When adhesive joints fracture, multiple failure modes are prone to coupling. Each failure mode has different degrees of influence on the energy absorption of joint fracture. The fracture toughness of various failure modes needs to be taken into account in the fracture model. In order to accurately and efficiently simulate the damage evolution process of hybrid structural adhesive joints with multiple failure modes coupling, the power exponential fracture model of type I, type II and type III fracture toughness coupling is expanded to a damage evolution model of all fracture toughness coupling of three failure modes (each failure mode contains three fracture toughnesses), in which the power exponential parameter is variable and used to describe the coupling effect between various fracture toughnesses. The following mathematical form of coupled failure fracture toughness is constructed to describe the damage evolution:

[0047]

[0048] In the formula, the numerator is the energy absorption value of each mode under the coupled failure mode defined at the initial moment of failure calculated based on the ratio relationship between the various stresses that meet the failure criterion at the initial moment of failure, G interAIC , G interAIIC , G interAIIIC are the energy absorption values ​​of type I, type II and type III fracture modes of interface failure between adhesive and base material A under stress coupling state at the moment of fracture, G interBIC , G interBIIC , G interBIIIC are the energy absorption values ​​of type I, type II and type III fracture modes of interface failure between adhesive and base material B under stress coupling state at the moment of fracture, G GlueIC , G GlueIIC , G GlueIIICare the energy absorption values ​​of type I, type II and type III fracture modes of the adhesive failure under stress coupling state at the moment of fracture; G in the denominator is interAI , G interAII , G interAIII are the energy absorption values ​​of type I, type II and type III fracture modes of the interface failure between the adhesive and the base material A when they exist separately, G interBI , G interBII , G interBIII are the energy absorption values ​​of type I, type II and type III fracture modes of the interface failure between adhesive and base material B when they exist separately, G GlueI , G GlueII , G GlueIII They are the energy absorption values ​​of the rubber itself when the type I, type II and type III fracture modes exist alone. 1 and β 1 It represents the coupling effect of three different fracture modes on the fracture behavior of the adhesive and base material A under the failure condition. The power exponent α 2 and β 2 Indicates the coupling effect of three different fracture modes on the fracture behavior of the adhesive and base material B under the failure condition. The power exponent α 3 and β 3 It represents the coupled influence of three different fracture modes on its fracture behavior when the adhesive fails. The power exponents of each item are obtained by inversely calculating the parameters through simulation curve fitting of type I and type II fracture test results of the coupled failure mode.

[0049] The above-mentioned type I, type II and type III fracture modes are shown in Figure 1 (a), (b), (c), which are opening type, sliding type and tearing type, respectively. The type II and type III fracture modes of the adhesive joints are shear in different directions, and the bonding area is a square. Therefore, it is believed that the energy absorption values ​​of type II and type III fracture modes when they exist alone are the same, that is, G interAII =G interAIII , G interBII =G interBIII , G GlueII =G GlueIII . The present invention obtains the type I fracture toughness (i.e., the energy absorption value when the fracture mode exists alone) through the DCB experiment, and obtains the type II and type III fracture toughness through the ENF experiment. The DCB experiment and the ENF experiment are schematically shown in Figures 2(a) and (b). The DCB specimen used to obtain the type I fracture toughness has a size of 180mmx25mm, and the pre-crack length is 50mm; the ENF specimen used to obtain the type II and type III fracture toughness has a size of 140mmx25mm, and the pre-crack length is 40mm. The positional relationship between the crack and the specimen is shown in Figure 2(a) and (b). Figure 3 shown.

[0050] 2. Parameter Acquisition Experimental Plan

[0051] All the required experiments are shown in Table 1. The specimens with a single failure mode in the table were subjected to type I and type II fracture tests and repeated three times. The experimental results were collated to obtain the fracture toughness parameters in the extended power exponential fracture model (i.e., the denominator in formula (1)). The specimens with three slopes and multiple failure modes coupled were subjected to type I and type II fracture tests once, and the power exponential parameters in the fracture model were inversely calculated by simulation fitting the experimental curves. The parent materials with three slopes refer to Figure 4 , where the adhesive specimen with slope 3 is Figure 5 shown.

[0052] Table 1 Experimental plan

[0053]

[0054]

[0055] 3. Fracture toughness parameter acquisition process

[0056] Step (1), preparing a sample for obtaining fracture toughness parameters

[0057] Three groups of homogeneous bonding specimens with type I, type II and type III fracture modes of interface failure between base material A and adhesive layer, three groups of homogeneous bonding specimens with type I, type II and type III fracture modes of interface failure between base material B and adhesive layer, and three groups of heterogeneous bonding specimens with type I, type II and type III fracture modes of self-cohesive failure between base material A and base material B were prepared. When preparing the specimens with interface failure between base material and adhesive layer, a certain length of polytetrafluoroethylene film needs to be placed between base material and adhesive layer to preform cracks, which is used to guide crack propagation and thus induce interface failure between base material and adhesive layer; when preparing the specimens with self-cohesive failure between adhesive layer, a certain length of polytetrafluoroethylene film needs to be placed in the middle of adhesive layer to preform cracks, which is used to guide crack propagation and thus induce cohesive failure of adhesive layer.

[0058] In order to prepare the specimen more accurately, the present invention also designs and manufactures a double cantilever beam (DCB) specimen / end notch bending (ENF) specimen preparation device for accurately customizing different failure modes of variable thickness heterogeneous adhesive joints, and the specimen preparation device includes tooling 1 and tooling 2. Figure 6 , 7As shown in , 8, the tool 1 includes a front plate 101 of the tool 1, a rear plate 102 of the tool 1, a bottom plate 103 of the tool 1, a pressure plate 104 of the tool 1, a DCB sample 105, a gasket 106 of the tool 1 and a feed screw 107 of the tool 1; the bottoms of the front plate 101 of the tool 1 and the rear plate 102 of the tool 1 are respectively connected to the two ends of the bottom plate 103 of the tool 1 by bolts, the bottom plate 103 of the tool 1 is stepped, and the front plate 101 of the tool 1 is installed on a higher level of the step, the rear plate 102 of the tool 1 is installed on a lower level of the step, and the pressure plate 104 of the tool 1 is placed between the front plate 101 of the tool 1 and the rear plate 102 of the tool 1, and is located on the lower level of the step; the widths of the front plate 101 of the tool 1 and the rear plate 102 of the tool 1 (perpendicular to the direction of the feed screw on the horizontal plane) are equal to the width of the bottom plate 103 of the tool 1 The tool 1 pressure plate 104 is consistent with the tool 1, the width of the tool 1 pressure plate 104 is smaller than the width of the tool 1 rear plate 102, and the tool 1 bottom plate 103 at both ends of the length direction (parallel to the direction of the feed screw) of the tool 1 pressure plate 104 is provided with bosses, and the outer side of the bosses is flush with the outer side of the tool 1 bottom plate 103; a threaded hole is provided on the tool 1 front plate 101, and the tool 1 feed screw 107 is installed and fixed through the threaded hole; grooves consistent with the size of the DCB sample are respectively provided in the center of the opposite surfaces of the tool 1 pressure plate 104 and the tool 1 rear plate 102, and the depth of the groove is lower than the thickness of the sample; in addition, a sampling groove for convenient sampling is reserved at the upper end of the groove, and a channel for convenient processing is reserved at the lower end; when the device is in use, the tool 1 gasket 106 is manually set on the upper and lower ends of the vertical direction of the side of the tool 1 rear plate 102 close to the tool 1 pressure plate 104.

[0059] like Fig. 9 As shown, tool 2 includes a tool 2 front plate 201, a tool 2 rear plate 202, a tool 2 bottom plate 203, a tool 2 pressure plate 204, an ENF sample 205, a tool 2 gasket 206 and a tool 2 feed screw 207, and its composition is consistent with that of tool 1 and will not be repeated here. Grooves consistent with the size of the ENF sample are respectively provided in the center of the opposing surfaces of the tool 2 pressure plate 204 and the tool 2 rear plate 202.

[0060] Furthermore, the steps for preparing DCB (ENF) specimens with failure at the interface between the base material and the adhesive layer or cohesive failure of the adhesive layer itself are as follows:

[0061] 1) Apply an appropriate amount of anti-sticking grease to the non-adhesive areas (except the areas of the sample) of the bottom plate, the pressure plate and the back plate grooves, and place the sample in the pre-opened grooves of the pressure plate and the back plate: when preparing the sample with failure at the interface between the parent material and the adhesive layer, place homogeneous samples in the two grooves; when preparing the sample with cohesive failure of the adhesive layer itself, place heterogeneous samples in the two grooves;

[0062] 2) When preparing the specimens with failure at the interface between the base material and the adhesive layer, place a polytetrafluoroethylene film of a specified length on the pre-crack area on the base material side and fix it on the pressing plate with transparent tape, then use a glue gun to evenly apply a proper amount of glue on the adhesive areas of the specimens on both sides; when preparing the specimens with cohesive failure of the adhesive layer itself, first evenly apply a proper amount of glue on the adhesive areas of the specimens on both sides, then place a polytetrafluoroethylene film of a specified length on the pre-crack area in the middle of the adhesive layer and fix it on the pressing plate with transparent tape;

[0063] 3) Select a gasket of appropriate thickness according to the thickness of the prepared sample glue layer. The gasket thickness h 5 (h 6 ) is the sample thickness (a 1 、a 2 ) and the thickness of the adhesive layer b minus twice the depth d of the groove (pre-opened by the pressure plate and the back plate), that is, h 5 / h 6 =a 1 / a 2 +b-2d;

[0064] 4) Place the selected gaskets on the non-adhesive areas on both sides of the press plate and the back plate, place the press plate parallel to the back plate on the bottom plate and push it by hand until the two samples on the press plate and the back plate are glued together;

[0065] 5) Keep your hand on the pressure plate and rotate the feed screw evenly to push the pressure plate to the gasket restraining position and apply preload force with a torque wrench;

[0066] 6) Fix the feed screw and send the tooling into a constant temperature box for adhesive curing. After the curing is completed, disassemble the tooling, take out the sample, remove the overflowed glue and pull out the polytetrafluoroethylene film to prepare the DCB (ENF) sample with cohesive failure of the glue layer or interface failure on the parent material side, that is, the homogeneous bonding sample and heterogeneous bonding sample required above.

[0067] Step (2), fracture toughness parameter acquisition experiment

[0068] Type I and type II fracture tests were performed on samples with three different failure modes, and six fracture toughness parameters were obtained. The specific experimental process and the acquisition of fracture toughness are as follows:

[0069] 1) First, a DCB experiment was carried out on the homogeneous bonded specimens with type I fracture mode of interface failure between the base material A and the adhesive layer and repeated three times. The experiment was carried out on an electronic stretching machine. The DCB experiment requires a specimen connector (Figure 10(a)) and a stretching fixture (Figure 10(b)). The width of the connector is consistent with that of the specimen. A through hole is opened in the middle of the connector to cooperate with the pin of the stretching fixture. Before the experiment, the connector and the specimen need to be glued and cured together at a constant temperature. The upper end of the stretching fixture is the clamping end, and the lower end of the fixture is the specimen connection end. There is enough space at the lower end for the width of the specimen connector. After assembly, the gap between the fixture and the specimen should not exceed 0.3 mm.

[0070] During the test, the specimen connector and the tensile fixture are assembled by means of a pin. The stretching machine clamps the upper and lower ends of the tensile fixture respectively. After loading begins, the upper clamping end is fixed and the lower clamping end moves at a specified rate. The specimen begins to tear under the action of tension. The coordination of the tensile fixture and the connector pin ensures that the specimen is always subjected to a force consistent with the tensile direction at the loading end.

[0071] The experimental valid data were processed and the mode I fracture toughness parameter of the interface failure between the base material A and the adhesive layer was obtained according to formula (2):

[0072]

[0073] In the formula, G IC is the I-mode interlaminar fracture toughness. This time, we are looking for the I-mode fracture toughness parameter (i.e. G interAI ), m is the flexibility curve fitting coefficient, obtained according to formula (3), P I is the critical load for crack growth, δ I Corresponding to P I Loading point displacement, W I is the width of the specimen, a I is the crack length.

[0074] The flexibility curve fitting coefficient m of a single specimen is calculated according to (3):

[0075]

[0076] Where k is the number of measurement points of a single sample, a i is the crack length before the i-th loading; P i is the crack length a i Extended critical load, δ i Corresponding to P i Loading point displacement.

[0077] Furthermore, ENF experiments were carried out on homogeneous bonded specimens with a type II fracture mode of interface failure between the base material A and the adhesive layer and repeated three times each. The ENF experiments were carried out on an electronic compressor and the ENF experiments were carried out on an electronic compressor under three-point bending conditions.

[0078] When conducting the ENF test, adjust the appropriate spacing between the lower rollers and fix them, place the sample in the middle of the two lower rollers, and make one lower roller higher than the other lower roller, so that the variable thickness sample is supported by the lower rollers, and the upper surface of the sample is squeezed by the upper roller in a horizontal state. The upper roller is pressurized at a specified loading rate, and the sample bends and tears under the load of the upper roller.

[0079] The experimental valid data were processed and the type II and type III fracture toughness parameters of the interface failure between the base material A and the adhesive layer were obtained according to formula (4):

[0080]

[0081] In the formula, G II / IIIC is the type II and type III fracture toughness. This time, we are looking for the type II and type III fracture toughness parameters (i.e. G interAII , G interAIII ), P II is the critical load for crack growth, δ II Corresponding to P II The displacement of the loaded point, a II is the effective crack length, W II is the width of the specimen, 2L II is the support roller span.

[0082] 2) The DCB test was carried out on the homogeneous bonded specimens with the I-type fracture mode of the interface failure between the base material B and the adhesive layer and repeated three times. The experimental process was the same as above. The effective experimental data were processed and the I-type fracture toughness parameter (i.e., G) of the interface failure between the base material B and the adhesive layer was obtained according to formula (2). interBI ).

[0083] Then, the ENF experiment was carried out on the homogeneous bonded specimens with the type II fracture mode of the interface failure between the base material B and the adhesive layer, and each experiment was repeated three times. The effective experimental data were processed and the type II and type III fracture toughness parameters (i.e., G interBII , G interBIII ).

[0084] 3) The DCB test was carried out on the heterogeneous bonded specimens with the I-type fracture mode of the self-cohesive failure of the adhesive layer and repeated three times. The experimental process was the same as above. The effective experimental data were processed and the I-type fracture toughness parameter (i.e., G) of the self-cohesive failure of the adhesive layer was obtained according to formula (2). GlueI ).

[0085] Then, the ENF experiment was carried out on the heterogeneous bonded specimens with the type II fracture mode of the self-cohesive failure of the adhesive layer and repeated three times. The effective experimental data were processed and the type II and type III fracture toughness parameters (i.e., G GlueII , G GlueIII ).

[0086] 4) Arrange the fracture toughness parameters obtained in the above steps and fill them into the denominator of the extended power exponential fracture model accordingly, so as to obtain the coupled failure extended power exponential fracture model with unknown power exponent.

[0087] 4. Power exponent parameter acquisition process

[0088] Step (1), preparing a sample for obtaining power exponential parameters

[0089] The bonding specimens of type I and type II fracture modes of three types of base materials A with different slopes and base materials B with equal thickness were prepared. During the preparation, there was no need to insert polytetrafluoroethylene film to create cracks between the adhesive layers, so that multiple failure modes coupling could occur naturally during the fracture process.

[0090] The specimens are prepared by the above-mentioned precisely customized double cantilever beam (DCB) specimen / end notch bending (ENF) specimen preparation device for different failure modes of variable thickness heterogeneous adhesive joints. During the preparation, a specimen with the same slope as the variable thickness specimen is pre-placed in the groove of the back plate or pressure plate to constrain the specimen, and then the variable thickness specimen to be glued is placed, so that the two variable thickness specimens are fitted together to ensure that the specimen bonding surface is level and the bonding thickness is consistent. The rest of the preparation process is the same as above.

[0091] Step (2), power exponent parameter acquisition experiment

[0092] DCB experiments were carried out on type I fracture mode bonded specimens of three different slopes of base material A and equal thickness base material B, and ENF experiments were carried out on type II fracture mode bonded specimens of three different slopes of base material A and equal thickness base material B. The joints and fixtures of the specimens were shared with those in the fracture toughness acquisition experiment, and the experimental process was the same as above.

[0093] The experimental data were sorted out and the force-displacement curves of each group of experiments were obtained. The corresponding three groups of mode I fracture toughness and three groups of mode II fracture toughness were calculated by equations (2) and (4) respectively. Based on the extended power exponential fracture model of heterogeneous adhesive joints proposed above, the six power exponents (i.e., α 1 , β 1 , α 2 , β 2 , α 3 , β 3) The experimental conditions of bonding test of three different slope base materials A and equal thickness base materials B are simulated to obtain the simulated force-displacement curves and calculate the corresponding three groups of type I fracture toughness and three groups of type II fracture toughness; the RSME (root mean square error) between the fracture toughness obtained by the experiment and the fracture toughness obtained by the simulation is used to evaluate the error of the simulation fitting (the specific process is the existing technology). When RSME < 0.05, the six groups of experimental results all meet the simulation accuracy requirements, and the power exponent of the simulation simulation is the required power exponent parameter; if it cannot be satisfied, another slope base material A and equal thickness base material B are introduced to prepare bonding specimens of type I and type II fracture modes and conduct DCB and ENF experiments respectively, and the experimental results are brought into the power exponent iteration of the simulation fitting fracture toughness value to determine the power exponent value that meets the accuracy requirements. And so on.

[0094] 5. The fracture toughness parameter and power exponent parameter are determined through the above process and substituted into formula (1) to be used as the fracture model in the constitutive model of the adhesive in the simulation of heterogeneous adhesive joints, accurately characterizing the coupled failure behavior of heterogeneous adhesive joints.

[0095] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.

Claims

1. A damage evolution characterization method for coupled failure behavior of heterogeneous adhesive joints, characterized by: (1) Construct an extended power exponential fracture model for coupled failure of adhesive joints: Where: G interAIC , G interAIIC , G interAIIIC are the energy absorption values ​​of type I, type II and type III fracture modes of interface failure between adhesive and base material A under stress coupling state at the moment of fracture, G interBIC , G interBIIC , G interBIIIC are the energy absorption values ​​of type I, type II and type III fracture modes of interface failure between adhesive and base material B under stress coupling state at the moment of fracture, G GlueIC , G GlueIIC , G GlueIIIC are the energy absorption values ​​of type I, type II and type III fracture modes of the adhesive failure under stress coupling state at the moment of fracture, G interAI , G interAII , G interAIII are the energy absorption values ​​of type I, type II and type III fracture modes of the interface failure between the adhesive and the base material A when they exist separately, G interBI , G interBII , G interBIII are the energy absorption values ​​of type I, type II and type III fracture modes of the interface failure between adhesive and base material B when they exist separately, G GlueI , G GlueII , G GlueIII are the energy absorption values ​​of the type I, type II and type III fracture modes of the adhesive itself when they exist alone, the power exponents α1 and β1 represent the coupling effects of the three different fracture modes on its fracture behavior when the interface between the adhesive and the base material A fails, the power exponents α2 and β2 represent the coupling effects of the three different fracture modes on its fracture behavior when the interface between the adhesive and the base material B fails, and the power exponents α3 and β3 represent the coupling effects of the three different fracture modes on its fracture behavior when the adhesive fails itself; the type I, type II and type III fracture modes are specifically opening type, sliding type and tearing type; (2) Three groups of homogeneous bonding specimens with three fracture modes of interface failure between base material A and adhesive layer, three groups of homogeneous bonding specimens with three fracture modes of interface failure between base material B and adhesive layer, and three groups of heterogeneous bonding specimens with three fracture modes of self-cohesive failure of adhesive layer were prepared by DCB specimen preparation device and ENF specimen preparation device respectively. When preparing specimens with interface failure between base material and adhesive layer, a pre-crack of polytetrafluoroethylene film was placed between base material and adhesive layer to guide crack propagation and thus induce interface failure between base material and adhesive layer. When preparing specimens with self-cohesive failure of adhesive layer, a pre-crack of polytetrafluoroethylene film was placed in the middle of adhesive layer to guide crack propagation and thus induce cohesive failure of adhesive layer. DCB experiments were carried out on the three types of bonding specimens with type I fracture mode, and the experimental data were processed to obtain G interAI , G interBI , G GlueI ; ENF experiments were performed on three types of adhesive bonding tests with type II fracture mode, and the experimental data were processed to obtain G interAII , G interAIII , G interBII , G interBIII , G GlueII , G GlueIII ; (3) The DCB specimen preparation device and the ENF specimen preparation device are used to prepare the bonding specimens of type I and type II fracture modes of the three types of base materials A with different slopes and base materials B with equal thickness respectively; the DCB test is carried out on the bonding specimens of type I fracture mode of the three types of base materials A with different slopes and base materials B with equal thickness respectively, and the ENF test is carried out on the bonding specimens of type II fracture mode of the three types of base materials A with different slopes and base materials B with equal thickness respectively; the force-displacement curve of each group of experiments is obtained from the experimental data and the corresponding fracture toughness value is calculated, each group of experimental working conditions is simulated, and the error analysis is carried out between the fracture toughness value obtained by the simulation result curve and the fracture toughness value obtained by the experiment through the updating and iteration of the power exponent. When RSME is less than 0.05, the accuracy requirement is met, and the power exponent of the simulation is the power exponent parameter required; (4) Determine G interAI , G interBI , G GlueI , G interAII , G interAIII , G interBII , G interBIII , G GlueII , G GlueIII The sum power exponent is substituted into formula (1) and used as the fracture model in the constitutive model of the adhesive in the simulation of heterogeneous adhesive joints to realize the simulation of the coupled failure behavior of heterogeneous adhesive joints.

2. The damage evolution characterization method of coupled failure behavior of heterogeneous adhesive joints according to claim 1 is characterized in that: The sample preparation device includes a front plate, a rear plate, a bottom plate, a pressing plate, a sample, a gasket and a feed screw, wherein the bottom plate is stepped; the bottom of the front plate is mounted on a higher level of the bottom plate step, and the feed screw is mounted on the front plate; the bottom of the rear plate is mounted on a lower level of the bottom plate step, and the pressing plate is placed between the front plate and the rear plate and is located on the lower level of the bottom plate step; grooves consistent with the size of the sample are respectively provided on the opposing surfaces of the pressing plate and the rear plate, and the depth of the grooves is lower than the thickness of the sample; when the device is in use, the gaskets are arranged at the upper and lower ends of the opposing surfaces of the rear plate and the pressing plate in the vertical direction.

3. The damage evolution characterization method of coupled failure behavior of heterogeneous adhesive joints according to claim 2 is characterized in that: The dimensions of the front plate and the rear plate on the horizontal plane perpendicular to the direction of the feed screw are consistent with those of the bottom plate, and the dimension of the pressure plate on the horizontal plane perpendicular to the direction of the feed screw is smaller than that of the bottom plate.

4. The damage evolution characterization method of coupled failure behavior of heterogeneous adhesive joints according to claim 2 is characterized in that: Bosses are arranged at two ends of the bottom plate on the moving path of the pressing plate toward the rear plate.

5. The damage evolution characterization method of coupled failure behavior of heterogeneous adhesive joints according to claim 2 is characterized in that: A sampling groove for convenient sampling is reserved at the upper end of the groove, and a channel for convenient processing is reserved at the lower end.

6. The damage evolution characterization method of coupled failure behavior of heterogeneous adhesive joints according to claim 1 is characterized in that: When preparing specimens with failure at the interface between the base material and the adhesive layer, first place a polytetrafluoroethylene film on the pre-crack area on the base material side and fix it on the pressing plate, and then evenly apply glue on the adhesive areas of the specimens on both sides; when preparing specimens with cohesive failure of the adhesive layer itself, first evenly apply glue on the adhesive areas of the specimens on both sides, and then place a polytetrafluoroethylene film on the pre-crack area in the middle of the adhesive layer and fix it on the pressing plate.

7. The damage evolution characterization method of coupled failure behavior of heterogeneous adhesive joints according to claim 2 is characterized in that: The thickness of the gasket is selected according to the thickness of the sample, and the thickness of the gasket is the sum of the thickness of the sample and the thickness of the adhesive layer minus twice the depth of the groove.

8. The damage evolution characterization method of coupled failure behavior of heterogeneous adhesive joints according to claim 1 is characterized in that: When conducting a DCB experiment, a connector and a tensile fixture are required. The upper end of the tensile fixture is the clamping end, and the lower end of the fixture is the sample connection end. Before the experiment, the connector and the sample are glued and cured together at a constant temperature. The pin at the lower end of the tensile fixture passes through the through hole in the middle of the connector to achieve the coordination between the connector and the tensile fixture.

9. The damage evolution characterization method of coupled failure behavior of heterogeneous adhesive joints according to claim 1 is characterized in that: When the DCB test was conducted on the bonded specimens of type I fracture mode of the base material A with three different slopes and the base material B with equal thickness, the thickness of the adhesive layer of the bonded specimens was the same and did not change due to the change of the base material thickness; when the specimens broke under the experimental loading, multiple failure mode coupling failure occurred.

10. The damage evolution characterization method of coupled failure behavior of heterogeneous adhesive joints according to claim 1, characterized in that: When the ENF test was conducted on the type II fracture mode bonded specimens of three different slopes of base material A and the same thickness base material B, the thickness of the adhesive layer of the bonded specimens was the same and did not change due to the change of the base material thickness; when the specimens were loaded in the experiment, the lower support roller on one side was higher than the lower support roller on the other side, so that the variable thickness specimen was supported by the lower support roller, and the upper surface of the specimen was squeezed by the upper support roller in a horizontal state.

Citation Information

Patent Citations

  • Crack performance measurement and optimization solution method for composite material glue joint structure

    CN105022898A

  • Coating interface bonding strength detection method and equipment

    CN109406390A